2015
DOI: 10.1161/circimaging.115.003865
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic Longitudinal Function as Predictor of Outcome in Patients With Sepsis

Abstract: In patients with sepsis assisted in a high-dependency observational unit, feasibility of assessments of left ventricular EF and GLS within 24 h from the hospitalization was acceptable and EF showed no prognostic relevance, whereas GLS showed a correlation with mortality rate potentially relevant in shorter more than in longer follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 40 publications
3
51
0
4
Order By: Relevance
“…14 Recent studies have demonstrated that a impaired myocardial deformation, as assessed by low GLS, seems to provide incremental prognostic information to LVEF about the risk of cardiovascular morbidity and mortality, especially when LVEF is relatively preserved. 3,4,6 Similar results are presented in the current issue of Circulation: Cardiovascular Imaging, where Palmieri et al 15 report an interesting article, which aims to investigate whether GLS provide incremental prognostic information in patients admitted to a subintensive medical unit with severe sepsis or septic shock. 15 This prospective study included 115 patients admitted to a single subintensive medical unit, who had an echocardiogram performed within 24 hours of admission.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…14 Recent studies have demonstrated that a impaired myocardial deformation, as assessed by low GLS, seems to provide incremental prognostic information to LVEF about the risk of cardiovascular morbidity and mortality, especially when LVEF is relatively preserved. 3,4,6 Similar results are presented in the current issue of Circulation: Cardiovascular Imaging, where Palmieri et al 15 report an interesting article, which aims to investigate whether GLS provide incremental prognostic information in patients admitted to a subintensive medical unit with severe sepsis or septic shock. 15 This prospective study included 115 patients admitted to a single subintensive medical unit, who had an echocardiogram performed within 24 hours of admission.…”
supporting
confidence: 52%
“…3,4,6 Similar results are presented in the current issue of Circulation: Cardiovascular Imaging, where Palmieri et al 15 report an interesting article, which aims to investigate whether GLS provide incremental prognostic information in patients admitted to a subintensive medical unit with severe sepsis or septic shock. 15 This prospective study included 115 patients admitted to a single subintensive medical unit, who had an echocardiogram performed within 24 hours of admission. Follow-up on mortality was assessed at 7 and 28 days after admission.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Although not large (198 evaluable subjects) and restricted to a single centre, this is the largest series to combine both measures and it is worth emphasising that this was a high-risk population. Almost 40% were diabetic and more than a quarter had an existing diagnosis of coronary artery disease.GLS using speckle tracking echocardiography has an expanding role in cardiology practice and has proved to be superior to left ventricular ejection fraction (LVEF) in predicting outcomes in situations as diverse as sepsis [2] , heart failure with preserved ejection fraction [3] and late after cardiotoxic chemotherapy [4] . As such, it is part of the repertoire of many cardiology departments.…”
mentioning
confidence: 99%